FUTURE OF ASPHALT DEVELOPMENT: A REVIEW OF SUSTAINABLE ADDITIVES AND ADVANCED TECHNOLOGIES FOR ENHANCED ASPHALT PERFORMANCE - Hussein Hatem Meteab; Amal Shakir Abbood; Ghufran Hamed Nail (Universitas Islam Sumatera Utara, 2025)
This review explores the latest advancements in enhancing asphalt performance, focusing on the use of additives that improve the properties of bitumen and fillers in asphalt mixtures. The study includes innovative materials such as calcite, quartz, various soils, liquid sulfur, Gil Sonite, traditional fillers, and polymeric additives. It also examines advanced materials like graphene oxide, biochar, and phase-change materials, and investigates the use of both natural and recycled rubber. Special attention is given to sustainable practices, highlighting the use of waste resources such as used motor oil, ceramic fibers, recycled asphalt aggregate, and leftover cooking oil. The review also looks into the integration of advanced technologies like microwave energy and synthetic fibers to enhance the performance and durability of asphalt. By summarizing current research and development efforts, this review provides an in-depth look at these innovations and their potential to revolutionize the asphalt industry. It discusses future prospects, including self-healing asphalt, digital tools for optimizing asphalt production, and autonomous maintenance systems. The review aims to support researchers, engineers, and policymakers in developing more durable, efficient, and sustainable asphalt solutions, offering a comprehensive assessment of the current state and future directions of asphalt enhancements. Through this review, stakeholders can gain a better understanding of current and future innovations that could significantly impact the development and maintenance of road infrastructure.